"Flashing into the crystal mirror" : the recurrence of the mirror motif in three Arthurian works - Lara Rallo, Carmen (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2004)
When constructing “The Lady of Shalott”, Tennyson resorts to the medieval atmosphere of King Arthur’s court to set a poem in which the development of the action is dictated by the pervasive force of a mirror. This object, which controls the Lady’s fate, is the one that rules the sense of duality existing in the “The Lady of Shalott”. Indeed, the duplications and contrasts on which the poem is based emerge from the encounter of symmetrical and opposing forces face to face, precisely the type of encounter which lies at the heart of the process of refraction in a mirror. In this sense, the mirror in Tennyson’s poem could be seen not simply as a physical object, but above all as the expression of a motif characterised by the phenomenon of optical repetition and all the processes literally or metaphorically emerging from it. In conflating the Arthurian theme and the exploration of this motif, Tennyson is reviving a pattern which underlies, on different levels, two significant works of the medieval English Arthurian body: Sir Gawain and the Green Knight and Le Morte Darthur. While in Sir Gawain the mirror is the source of the symmetrical structure of the poem, the influence of the mirror motif in Le Morte appears under the form of a multi-shaped duality. The aim of this paper is to investigate the way in which the mirror motif recurs in these three Arthurian works.